Strategic priorities of innovative entrepreneurship development in agrarian sector - Yakobchuk V. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The author substaintiates the methodological principles and the technique of the research of strategic priorities on the innovative development of Ukraine’s enterprises in agrarian sector of the economy. The author also improves the technique of applying SWOT-analisis of agrarian enterprise innovative development in combination with the method of simulating innovative changes.